2022
DOI: 10.3390/ijerph19074037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bioelectrical Impedance Analysis with DXA in Adolescents with Cystic Fibrosis before and after a Resistance Training Intervention

Abstract: Background: The purpose of this pilot study was to compare body composition metrics obtained by two portable bioelectrical impedance analysis (BIA) devices with dual-energy X-ray absorptiometry (DXA) among adolescents with cystic fibrosis (CF) before and after a resistance exercise training program. Methods: Participants with CF were assessed using DXA, single-frequency BIA (SFBIA), and multiple-frequency BIA (MFBIA) to quantify percent body fat (%Fat), fat mass (FM), and fat-free mass (FFM) at baseline and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…24,25 REDCap is a secure, web-based software platform designed to support data capture for studies, Differences in FM and FFM measured by DXA and BIA at baseline and week 16, and changes in FM and FFM were compared using paired t-tests. [26][27][28] Body composition by DXA was compared separately to each BIA position. Differences with a p-value <0.05 were considered significant.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 REDCap is a secure, web-based software platform designed to support data capture for studies, Differences in FM and FFM measured by DXA and BIA at baseline and week 16, and changes in FM and FFM were compared using paired t-tests. [26][27][28] Body composition by DXA was compared separately to each BIA position. Differences with a p-value <0.05 were considered significant.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even dual-frequency BIA can show large differences from DXA 31 . In studies of obese and diseased children, single-frequency BIA has shown discrepancies with DXA 32 , 33 . Impedance is a function of reactance and resistance 28 , 34 , and a potential solution to this problem is to incorporate technology that can measure reactance, making it possible for even a single-frequency BIA device to acquire information that reflects not only the resistance of the extracellular fluid, but also information from the cell membrane, thereby improving the accuracy of the measurements.…”
Section: Introductionmentioning
confidence: 99%